Effects of left anodal transcranial direct current stimulation on hypothalamic-pituitary-adrenal axis activity in depression: a randomized controlled pilot trial - Pedraz Petrozzi, Bruno; Ferreira Pina Baptista Sardinha, Helena Maria; Gilles, Maria; Deuschle, Michael (Scientific reports, 2023)
The main objective of this study was to evaluate the effect of left anodal transcranial direct current stimulation (tDCS) on hypothalamic-pituitary-adrenal axis (HPAA) activity in individuals with depression. We conducted a 3-week, randomized, triple-blind pilot trial with 47 participants (dropout rate: 14.89%) randomly assigned to either the tDCS or control group (sham stimulation). Salivary cortisol was used as an HPAA activity marker since cortisol is the effector hormone of the HPAA. The primary outcome was the effect of tDCS on the diurnal cortisol pattern (DCP and area under the curve with respect to ground -AUCg-). Secondary outcomes included tDCS effects on cortisol awakening response (CAR) and cortisol decline (CD), as well as the variation of cortisol concentrations between the initiation of tDCS and 2 weeks later. Intention-to-treat and per-protocol analyses were conducted. Our primary outcome showed an absent effect of tDCS on DCP and AUCg. Additionally, tDCS had an absent effect on CAR, CD, and cortisol concentration variation before-after stimulation. Our pilot study suggests that anodal tDCS showed an absent effect on HPAA activity in individuals with depression. More studies are needed to confirm these findings.